Aplicação da simulação empresarial no ensino da graduação - Soares de Oliveira, Fernando Porfírio; Reis de Souza, Renata Laise; e Medeiros Júnior, Josué Vitor; Anez, Miguel Eduardo Moreno (Revista Gestão da Produção Operações e Sistemas, 2007)
This proposal develops methodological and didactic activities seeking the assimilation of the content taught inthe classroom as well as at a distance, through the use of simulation software as a support tool to the teachingand learning practices. As a result, the systemic thinking is stimulated, making available not only the simulationitself – both in the classroom as well as at a distance – but also in a structure that enables the students tounderstand how the interrelations determine the behavior of organizational systems and/or how their decisionsin specific parts of the system impact on other parts, in time and space.Taking it into consideration, one moves towards a pedagogic practice based on systemic education, in which thestudents cannot only assimilate concepts, but also interact with these concepts, question their assumptions anddecisions – mainly in an experimentation exercise based on the construction and reconstruction of simulationmodels of a certain “reality” characterized by its dynamic complexity. The methodology is grounded on themodeling process of the organizational realities proposed by Sterman (2000).Keywords: System dynamics, business simulation, systemic education, system modeling, production engineeringteaching.